Feeling Academic in the Neoliberal University Feminist Flights, Fights and Failures (Palgrave Studies in Gender and Education,, 2018)
This book offers a contemporary account of what it means to inhabit academia as a privilege, risk, entitlement or a failure. Drawing on international perspectives from a range of academic disciplines, it asks whether feminist spaces can offer freedom or flight from the corporatized and commercialized neoliberal university. How are feminist voices felt, heard, received, silenced, and masked? What is it to be a feminist academic in the neoliberal university? How are expectations, entitlements and burdens felt in inhabiting feminist positions and what of 'bad feeling' or 'unhappiness' amongst feminists? The volume consider these issues from across the career course, including from 'early career' and senior established scholars, as these diverse categories are themselves entangled in academic structures, sentiments and subjectivities; they are solidified in, for example, entry and promotion schemes as well as funding calls, and they ask us to identify in particular stages of 'being' or 'becoming' academic, while arguably denying the possibility of ever arriving. It will be essential reading for students and researchers in the areas of Education, Sociology, and Gender Studies.